2017
DOI: 10.15252/emmm.201708078
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Pneumoviridae fusion proteins as immunogens to induce cross‐neutralizing antibody responses

Abstract: Human respiratory syncytial virus (hRSV) and human metapneumovirus (hMPV), two members of the Pneumoviridae family, account for the majority of severe lower respiratory tract infections worldwide in very young children. They are also a frequent cause of morbidity and mortality in the elderly and immunocompromised adults. High levels of neutralizing antibodies, mostly directed against the viral fusion (F) glycoprotein, correlate with protection against either hRSV or hMPV. However, no cross‐neutralization is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Multiple protein engineering strategies have been investigated to generate cross-protective or epitope-based antigens against RSV F or hMPV F. Previous attempts at grafted a single antigenic site on RSV F or hMPV F from one to another induced cross-neutralizing antibodies but very limited protection against the heterologous virus challenge, likely due to the epitopes on the backbone still dominate the immune responses (39). RHMS-1 contains multiple immunodominant epitopes of both RSV F and hMPV F in relatively equal propotions, including at least three RSV F-specific and three MPV F-specific antigenic sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple protein engineering strategies have been investigated to generate cross-protective or epitope-based antigens against RSV F or hMPV F. Previous attempts at grafted a single antigenic site on RSV F or hMPV F from one to another induced cross-neutralizing antibodies but very limited protection against the heterologous virus challenge, likely due to the epitopes on the backbone still dominate the immune responses (39). RHMS-1 contains multiple immunodominant epitopes of both RSV F and hMPV F in relatively equal propotions, including at least three RSV F-specific and three MPV F-specific antigenic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the similarities between RSV and hMPV F, researchers have tried to generate universal RSV/MPV vaccines by grafting the helix-turn-helix motif (site II) from RSV F onto hMPV F, however, this chimera induced neutralizing antibody responses only to hMPV, but not RSV (38). A similar study that grafted RSV F and hMPV F epitopes on pre-fusion and pos-fusion F proteins showed that chimeric proteins swapping either site II or site IV can induce cross-neutralizing antibodies in mice, but a challenge with pre-fusion candidates was lacking (39). For the influenza hemagglutinin (HA) protein, chimeric immunogens generated by swapping the HA head with zoonotic subtypes while retaining the conserved HA stem successfully induced antibodies targeting the subdominant HA stem (40, 41).…”
Section: Introductionmentioning
confidence: 99%
“…The tools described herein provide the opportunity to identify other antigenic determinants in related morbilliviruses, for the ultimate development of pan-protective vaccines against another morbilliviruses. Such a concept has recently been exploited in the newly created Pneumoviridae family, separate from the original Paramyxoviridae family [94,95]. Thus, chimeric fusion protein consisting of respiratory syncytial virus and human metapneumovirus were shown in mice to induce cross-neutralizing immune responses [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…However, reinfections among the immunocompromised and the elderly can lead to more severe disease such as bronchiolitis and pneumonia (Boivin et al, 2002; Boivin et al, 2007; Walsh et al, 2008). Although vaccines and monoclonal antibodies are in various stages of early clinical development (Biacchesi et al, 2005; Chupin et al, 2021; Cox et al, 2014; Cseke et al, 2007; Hamelin et al, 2007; Herfst et al, 2008; Huang et al, 2021; Karron et al, 2018; Levy et al, 2013; Olmedillas et al, 2018; Schuster et al, 2015; Stepanova et al, 2020; Stewart-Jones et al, 2021), there are currently no FDA-approved interventions available. To develop an effective hMPV countermeasure, it will be important to have a thorough understanding of the humoral immune response that is elicited by natural infection.…”
Section: Introductionmentioning
confidence: 99%